Participatory implementation of an antibiotic stewardship programme supported by an innovative surveillance and clinical decision-support system. Issue 3 (November 2018) - Simões, A.S.; Maia, M.R.; Gregório, J.; Couto, I.; Asfeldt, A.M.; Simonsen, G.S.; Póvoa, P.; Viveiros, M.; Lapão, L.V.
Summary: Background: Antibiotic resistance will cause about 10 million deaths per year by 2050. Fighting antimicrobial resistance is a health priority. Interventions aimed to reduce antimicrobial resistance, such as antibiotic stewardship programmes (ASPs), must be implemented. To be effective, those interventions, and the implementation process, should be matched with social–cultural context. The complexity of ASPs can no longer be developed without considering both organizational and information systems. Aim: To support ASPs through the co-design and implementation, in collaboration with healthcare workers, of a surveillance and clinical decision-support system to monitor antibiotic resistance and improve antibiotic prescription. Methods: The surveillance and clinical decision-support system was designed and implemented in three Portuguese hospitals, using a participatory approach between researchers and healthcare workers following the Design Science Research Methodology. Findings: Based on healthcare workers' requirements, we developed HAITooL, a real-time surveillance and clinical decision-support system that integrates visualizations of patient, microbiology, and pharmacy data, facilitating clinical decision. HAITooL monitors antibiotic usage and rates of antibiotic-resistant bacteria, allowing early identification of outbreaks. It is a clinical decision-support tool that integrates evidence-based algorithms to support proper antibiotic prescription. HAITooL was considered valuable to support monitoring of antibiotic resistant infections and an important tool for ASP sustainability. Conclusion: ASP implementation can be leveraged through a surveillance and clinical decision-support system such as HAITooL that allows antibiotic resistance monitoring and supports antibiotic prescription, once it has been adapted to the context and specific needs of healthcare workers and hospitals.